The Impact of Canva Media in Creating Posters to Enhance Learning for 4th Grade Students at Singgersing Elementary School: A Literature Review - ismal J Andika (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study investigates the impact of Canva media in creating posters as a strategy to enhance learning outcomes for 4th-grade students at Singgersing Elementary School. In today's digital era, the integration of technology in education is essential for fostering student engagement and improving learning processes. Posters, as a visual learning medium, play a crucial role in conveying information effectively, making complex concepts more accessible. Canva, a graphic design platform, provides users with the tools to create visually appealing posters, allowing teachers and students to collaborate creatively. This literature review examines various scholarly articles and research findings that demonstrate the advantages of using Canva in educational settings. Results indicate that the use of Canva not only increases student motivation and participation but also improves comprehension and retention of learning material. As a result, this study advocates for the incorporation of digital design tools like Canva in the curriculum to promote better learning experiences and outcomes for elementary school students.